A educação profissional e tecnológica na 20ª CRE: o impacto dos protocolos governamentais para o ensino durante a pandemia de Covid-19 - Geiss, Eno Renato (2023)
This research, carried out with the Master's Program in Professional and Technological Education (PPGEPT - UFSM), presents the impact caused by the application of the government protocols for teaching in the Professional Education schools of the 20th Regional Education Coordination (20th CRE) of Rio Grande do Sul (RS). Faced with the pandemic scenario in the country, in 2020 and 2021, education underwent several changes imposed by government decrees and by the COVID-19 virus itself. In record time, all educational institutions had to adapt to a new reality and teaching strategies, with Emergency Remote Education (ERE) being the main action developed by schools in RS, followed by the hybrid teaching method. As a result, the ERE and hybrid teaching made it possible to continue the pedagogical activities in most schools throughout Brazil, guaranteeing the continuity of teaching by law. Therefore, in the context of Professional and Technological Education (EPT), it was no different. Thus, this Master dissertation aimed to assess the impact of ERE and hybrid teaching method on teaching in five EPT courses in two state schools in the 20th CRE in Palmeira das Missões - RS. To this end, we carried out a qualitative study and a case study, which allowed us to analyze how teachers and students faced this change in teaching strategy in practice. To produce the data, the State Education Department (SEDUC RS) system was consulted, focusing on data on school dropouts, enrollment cancellations, loss of contracts and teacher salary cuts. A questionnaire with open and closed questions was administered to teachers and students to check their adaptation to and analysis of the ERE and hybrid teaching method. The research pointed out mistakes and successes with the application of the educational process lived and brings suggestions and improvements in the educational process in a situation of health crisis or other possible problems that can resume this post-pandemic emergency planning.